التاريخي والتخييلي في رواية " تشرفت برحيلك" لفيروز رشام - عديلية, لمياء; سعدون, سالم (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الدراسة إلى المساهمة في قراءة الإنتاج الأدبي الروائي الجزائري المعاصر، الذي يتمحور حول التاريخ الجزائري و الذي أخذ على عاتقه إعادة بعثه من جديد من خلال إعادة استنطاق هذا التاريخ و مساءلته وتفكيكه، وتركيبه ، ومحاورته وفق استراتيجيات تخييلية تصور الواقع من جهة وتتجاوزه من جهة أخرى من خلال مجموعة من الآليات التي تفرضها الكتابة الروائية والمخيال الإبداعي ضمن قالب فني لغوي جمالي، وانطلاقاً من دراسة تمازج التاريخ ذي المرجعية الواقعية في السرد الروائي ذي المرجعية الخيالية في رواية " تشرفت برحيلك" باعتبارها رواية معاصرة تناولت فترة العشرية السوداء كموضوع و الذي لازال يلقى رواجاً كبيراً في حقل الرواية الجزائرية. This paper aims at contributing to the reading of the Algerian, contemporary, literary and novelistic production that deals with the Algerian history . A production which shoulders the responsibility to revive this history by questioning it, decoding it, encoding it and interacting with it according to imaginative strategies which show reality, on one hand, and go beyond it on the other, through a number of techniques imposed by the novelistic writing and the creative imagination an artistic, linguistic and aesthetic form. Our corpus in this paper is a novel including a mixture of history characterized by a realistic reference and the novelistic narration characterized by an imaginative reference. We have studied Tasharaftu Birahilika (delighted with your departure) novel as a contemporary novel dealing with the black decade period, a topic that is still widely dealt with in the Algerian novel
The Historical Reality And Narrative Imaginative In Tasharaftu Birahileka Novel By Fairouz Recham
مقال
Keywords: متخيل تخييل خيال سرد تاريخي